2014
DOI: 10.1097/mnm.0000000000000028
|View full text |Cite
|
Sign up to set email alerts
|

Painful knee prosthesis

Abstract: SPECT/CT is a useful tool for the evaluation of painful knee prosthesis in 85.5% of cases and helps in confirming mechanical loosening and in excluding other causes such as infection and patellofemoral osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In addition, previous studies were not able to establish a clear correlation between clinical and radiological outcomes [15, 16, 21, 39, 40]. However, controversial results have been published in recent studies analysing the clinical value of SPECT/CT in patients with knee pain [3, 28, 29, 32]. It is currently still unclear whether BTU shows a significant correlation with clinical outcome parameters in patients with OCL.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies were not able to establish a clear correlation between clinical and radiological outcomes [15, 16, 21, 39, 40]. However, controversial results have been published in recent studies analysing the clinical value of SPECT/CT in patients with knee pain [3, 28, 29, 32]. It is currently still unclear whether BTU shows a significant correlation with clinical outcome parameters in patients with OCL.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Nabhani [ 40 ] reported on 24 patients with painful knee prostheses who underwent revision surgery. With a medium risk of bias under the QUADAS-2 tool (explained by the flow and timing domain), they achieved a SEN of 0.90 [95% CI: 0.55–1.00] and a SPE of 0.95 [95% CI: 0.86–0.99] for SPECT/CT in identifying the source of pain, ultimately confirming the diagnosis in 21 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Rasch et al [ 47 ] found a significant correlation between valgus alignment of the femoral component and increased BTU in the lateral patellar areas ( P < 0.005). The use of this image scheme was also important for defining particular BTU patterns associated with specific conditions, such as malpositioning of the components, maltracking, patellar overloading, patellar osteoarthritis and loosening, which led the clinician to change the initial diagnosis in up to 85% of the patients [ 40 , 41 , 46 ]. It is important to highlight a recent report by Mathis et al [ 21 ], which showed a significant correlation ( P < 0.05) between different patterns of BTU and the position of the TKA components together with different pain patterns, enhancing the importance of the component position as a potential source of pain in painful knee arthroplasty patients.…”
Section: Discussionmentioning
confidence: 99%
“…SPECT/CT showed that patella uptake was associated with treatment response and severity of patellar condral lesions [ 55 ]. Similar to painful hip prosthesis, In patients with painful knee prostheses, SPECT/CT could diagnose accurately infection and prosthesis loosening and had clinical impact on 85.5% of patients [ 56 ].…”
Section: Main Bodymentioning
confidence: 99%